ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INITIAL TRUST SERTA DAMPAKNYA TERHADAP MINAT BELI KONSUMEN PADA TOKO ONLINE LAZADA INDONESIA - Maharani, Shabira; Indriani, Farida (Diponegoro Journal of Management, 2017)
This research aims to analyze the influence of perceived corporate reputation, perceived corporate size, perceived ease of use, and perceived website security towards the customer’s purchase intention of Lazada Indonesia online store through initial trust as the intervening variable.The sampling method used on this research is non-probability sampling with purposive sampling technique. Samples were collected from 100 respondents on Semarang who knows the information about Lazada Indonesia and have visited Lazada Indonesias’s website. Analysis method used here is multiple regression analysis which includes validity test, reliability test, classic assumption test, multiple linear regression test, t-test, f-test, determination test and sobel test.The result showed that perceived corporate reputation, perceived corporate size, perceived ease of use and perceived website security has positive and significant influence towards the initial trust. While initial trust as the intervening variable has positive and significant influence towards the purchase intention.